THE EFFECTIVENESS OF USING COOPERATIVE LEARNING MODEL OF GROUP INVESTIGATION AND THINK PAIR SHARE ON THE MATHEMATICS LEARNING OUTCOMES OF THE EIGHT-GRADE STUDENTS - Riska Kurniati; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Mathematic learning for the eighth-grade students at Muhammadiyah Junior high School Banguntaoan (SMP Muhammadiyah Banguntapan) Yogyakarta uses lecture method, discussion, and question and answer, which resulted in the students less enthusiastic during the mathematic lessons. Also, the mathematics lesson that is considered difficult, and the method is considered less fun is an obstacle for students to get a satisfactory mark. This research aims to find whether there are differences on students' result of learning mathematics using group investigation learning model and think pair share learning model and to compare the effectiveness of both models on the result of learning mathematics of the eighth-grade students of even semester at SMP Muhammadiyah Banguntapan Yogyakarta in the academic year 2016/2017. This research population is the eighth-grade students of SMP Muhammadiyah Banguntapan, which are class VIIIA, VIIIB, and VIIIC. The sample of this research is taken from two classes using a random sampling technique for the classes. It is obtained from the experiment class VIIIB and the experiment class VIIIA. The design of this research is the posttest-only control design. The data collection is obtained using the test method. The instrument is tested using validity, reliability, and different potency test. The data analysis technique used for prerequisite analysis tests is the normality test, homogeneity test, and hypothesis test. The result of this research at a significant level 5% and df= 60 indicates that: (1) There are differences in the students' learning mathematics results using the group investigation learning model and Think Pair Share learning model. It is showed by the value of and  so that  and (2) group investigation learning model is more effective than Think Pair Share learning model on the students’ result of learning mathematics. It is indicated by the value of and  so that .